Foundations of Joomla! - Harwani, Bintu. (Apress : Imprint: Apress, 2015)
Foundations of Joomla is a step by step practical guide that explains building web sites and blogs using Joomla - a very popular and powerful content management system (CMS). The book takes you through the steps of installing Joomla, configuring your database, creating a blog and a website, followed by instructions on creating new posts and adding content to your site. Even if you are an absolute beginner and don't have any programming experience, you can build responsive, powerful, and fully featured websites quickly. Following clear and easy to understand instructions, you'll master Joomla 3 by building a sample site throughout the book.